Cetacaine Spray as an Ex Vivo "Plastic-on-Plastic" Lubricant for Airway Management Procedures: A New Use for Dipropylene Glycol?. Issue 3 (July 2018) - Atlas, Glen; Sheikh, Usman
Abstract : In addition to being an aerosolized topical local anesthetic, Cetacaine Spray has the physical property of being an excellent medical lubricant for airway management and related procedures. This is a result of the constituent ingredient dipropylene glycol (DPG). However, because of the presence of benzocaine, this medication can cause methemoglobinemia if absorbed excessively. The authors speculate that aerosolized DPG may be useful as medical lubricant, independent of the local anesthetics contained within Cetacaine Spray. Further research into this potential application of DPG may be indicated.